ACARA PERAGAAN BUSANA "TRUCE: THE TRUE ELUCIDATION OF CYBERBULLYING" - Veby Sabrina Firdaus (Commed : Jurnal Komunikasi dan Media, 2018)
Internet is one of the newest medias that has been commonly used by the public. One of the problems which has been happening very often lately is the misuse of the internet mostly done by teenagers in Indonesia on social media, where social media is often used as a tool of cyberbullying. This fact is the main reason why the creators made an event that is also a campaign to spread awareness and invitation to not do cyberbullying with the social media influencers and teenagers as our main target audience. The event was a fashion show mixed with theatre acting and hip hop music. The main theme shown for this fashion show is Street Style with a touch of hip hop music because lately, hip hop is one of the popular music genres among society, especially the young people. Hip hop is considered to be a popular genre because it is known for its critical lyrics with deep meanings. The creators use theories such as Event Management Theory, Fashion Show Theory, Music Theory, Theatrical Theory, Social Criticism Theory, Social Message Theory, Cyberbullying Theory and Social Media Theory. The main theories that are used are Campaign Theory and K. Berlo's Communication Theory. The creators held this event entitled “TRUCE" which means The True Elucidation of Cyberbullying. The creators hope that this event will have an effect in the eyes of the general public and prevent themselves to not do cyberbullying.